Pearls and Pitfalls in Applying PI-RADS 2.1 - Ankur Pandey; Soumyadeep Ghosh; Priyanka Prajapati; Nabih Nakrour; Mukesh Harisinghani (Thieme Medical and Scientific Publishers Pvt. Ltd., 2024)
The use of Prostate Imaging Reporting and Data System (PI-RADS) with multiparametric magnetic resonance imaging (MRI) has significantly improved the detection of clinically significant prostate cancer (csPCa), but there are certain challenges that the reader may face. This review provides an overview of the pitfalls associated with the PI-RADS system for multiparametric prostate MRI (mpMRI), with suggestions/pearls to help overcome these pitfalls.